Throwing the Baby Out With the Bath Water: Could Widespread Neutering of Companion Dogs Cause Problems at a Population Level? - Dawson, Jessica K.; Howell, Tiffani J.; Ruby, Matthew B.; Bennett, Pauleen C. (Frontiers in Veterinary Science, 2019)
In many countries where companion dogs are popular, owners are strongly encouraged to neuter their dogs. Consequently, millions of dogs are neutered each year. In recent times considerable attention has been paid to the possible effects of such procedures on canine health and welfare. Less scrutinized are the potential ramifications of widespread neutering on the breeding of dogs and their continued success as human companions. This paper summarises research investigating factors influencing the breeding and rearing of dogs most suited to companionship roles in contemporary, typically high-density, communities, and briefly reviews current breeder practices. It then argues that a fundamental shift to promote inclusion of ‘proven’ companion dogs in the gene pool, as opposed to dogs meeting conformation or working/sporting standards, is required to successfully meet the needs of modern urban dog owners. A new model is proposed, whereby responsible owners and breeders work together to produce dogs most suited for life as human companions.